Peningkatan Motivasi dan Hasil Belajar Peserta Didik pada Pembelajaran Comparison Degrees melalui Lingkar Tiga Warna - Ratna Wahyudiati Hidayat (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
The Three Color Circle is a learning medium in English subject that aims to increase the motivation and learning outcomes of students in learning comparison degrees at class VIII SMP Negeri 4 Balikpapan. This research method uses classroom action research (CAR) by adopting Kemmis& Mc Taggart model. The procedure of this research was carried out in two cycles and divided into four activity stages in each cycle. In each stage consists of planning, acting, observing, and reflecting. The result of this research as follows: 1. 97,1% of the students were highly motivated in learning comparison degrees by using the three-color circle medium. 2. Significant students learning outcomes is 83% compared to before the research 71.4%. 3. Using of three-color circle medium in learning comparison degrees is very helpful for students.